Valuing Mental Health in the Justice System - Lugo, Anabel (2021)
Mental health is an issue that needs more recognition, especially within inmates and law enforcement. The mental health of incarcerated inmates, as well as law enforcement officials, has been overlooked and negatively impacted our criminal justice system. Ignoring mental health has helped create negative depictions and stereotypes about these communities. Law enforcement tends to ignore its mental health due to masculinity and police culture, feeding into the stigma that lingers around it. Although mental health has become a recurring topic in recent years, little has been done to help restore it within our justice system. Recently, there have been numerous incidents of police brutality, as well as rising numbers of incarcerated individuals, resulting in a negative image of both parties. Actions such as providing proper training to correctional facility staff, providing mental health resources to law enforcement, and creating a healthier environment for inmates are needed in order to create a better atmosphere within the justice system. By reforming and taking value in the mental health of both parties, our justice system can be reconstructed to place more value in mental health